Reconstruction of E-Court Legal Culture in Civil Law Enforcement (Journal of Indonesian Legal Studies, 2022)
Legal protection for the community to obtain rights and recovery of the situation is one of them taken by settling civil cases through the courts. During the times and the adjustment of existing conditions, the Supreme Court issued a responsive and progressive law with the enactment of Supreme Court Regulation Number 1 of 2019 so that the public could obtain essential justice based on the principles of fast, simple, and low-cost justice. The aims of this study are: (i) knowing the legal culture in the implementation of e-court as a reflection of the problems of law enforcement; and (ii) reconstruction of legal culture regarding case administration and court proceedings electronically. The author uses empirical juridical research methods. The results of the study show: (i) e-court based court legal culture is not yet optimal. Village communities seeking justice (non-advocates) at the Religious Courts and District Courts of Semarang Regency tend to prefer conventional registration and trial over e-courts; and (ii) the reconstruction of the legal culture community is carried out using e-court socialization education to all advocates, providing educational media to non-advocates, and providing information about administration and trials electronically through notification letters to the district head .Through this, it will create a legal culture that supports the implementation of e-court so that fair law enforcement can be achieved.